Investigating the psychological impact of COVID-19 on healthcare workers in the intensive care unit - Sünnetçi Silistre, Eda; Hatipoğlu, Halil Uğur; Yeşilbaş, Osman; Şükrü Gürbüz, Filiz; Ozturk, Erdogan; Yalçınkaya, Ahmet (Journal of Surgery and Medicine, 2022)
Background/Aim: The disease caused by the SARS-CoV-2 virus, COVID-19, has become the first viral disease outbreak defined as a pandemic in the 21st century. Experience with previous endemics shows that critical care workers disproportionately suffer from depression and anxiety after facing such outbreaks; however, data are limited regarding the early phase of spread. Our aim was to investigate depression and anxiety in healthcare workers employed in ICUs during the initial phase of COVID-19 spread in Istanbul, Turkey, and possible relationships with various characteristics of healthcare workers. Methods: This cross-sectional study evaluated descriptive and demographic characteristics, professions, COVID-19-related perceptions, depression and anxiety in healthcare workers from the 12 ICUs of six hospitals located in Istanbul, Turkey. The Beck Depression (Beck-D) and Anxiety (Beck-A) Inventories and the State-Trait Anxiety Inventory (STAI) TX-I and TX-II were used to assess depression and anxiety. Employees that worked in ICUs were included, regardless of profession, ICU type (neonatal/pediatric or adult), age, education and working status. We compared recorded data among employees with regard groups based on ICU type, sex, education status, profession, marital status, children, cohabiting status, and whether they were residing at their home. Additionally, multivariable regression analyses were performed to identify factors that were independently associated with scores obtained from the depression and anxiety scales. Results: A third of the studied population were found to have moderate-to-severe levels of depression and anxiety according to the Beck-D and Beck-A scales. The STAI TX-I scores were similar in all comparison groups except for significantly higher scores in participants living with their family/friends (P=0.027). STAI TX-II scores were higher in pediatric/neonatal ICU workers (P=0.001), nurses (P=0.002), employees without children (P=0.046), and those residing in their home (P=0.031). Beck-D scores were higher in nurses (P=0.001), those with lower education (P=0.025), subjects without children (P=0.008) and individuals living with their family/friends (P=0.002). Beck-A scores were higher in participants with lower education (P=0.001), nurses (P<0.001), those without children (P=0.049), subjects living with their family/friends (P=0.001), and those not residing in their home (P=0.003). There were only weak correlations between COVID-19-related perceptions and scale scores. Multivariable regression showed that being a physician and living alone were independently associated with lower Beck-D and Beck-A scores. Conclusion: The psychological impact of COVID-19 seems to be unassociated with disease-related perceptions during the early spread of disease, but about a third of ICU employees were found to have clinically-relevant levels of depression and anxiety. Our results show that nurses should receive continuous mental assessment and support, and that ICU employees may benefit from being provided with accommodation when caring for patients with diseases such as COVID-19.